Repetition and the Frame - Jennifer Yoos; Vincent James (Oz, 2000)
In his studies of animal locomotion, Eadweard Muybridge inadvertently developed the motion picture. By recombining the photographs extracted from life and projecting them in a rapid sequence, he recreated the motion of his subject. Ed. Note: The project is a boathouse for the Minneapolis Rowing Club, Minneapolis, MN.